Cerebral vasculitis and intracranial multiple aneurysms in a child with Lyme neuroborreliosis - Elisa Kortela; Jukka Hytönen; Jussi Numminen; Margit Overmyer; Harri Saxen; Jarmo Oksi (The Microbiology Society, 2025)
Introduction. Lyme borreliosis is a multisystem tick-borne disease caused by Borrelia burgdorferi. Neurological manifestations are reported in up to 15 % of adult patients with Lyme disease, while the frequency among children is higher. The most common manifestations are painful radiculopathy, facial nerve paresis and lymphocytic meningitis. Epileptic seizures and cerebral vasculitis with stroke or aneurysms are very rare complications. Case presentation. We describe a paediatric patient with sensorineural auditory dysfunction, headache, fatigue and epileptic seizures as sequelae of meningoencephalitis/Lyme neuroborreliosis (LNB) caused by B. burgdorferi. Brain magnetic resonance imaging revealed widespread enhancement of the leptomeninges, cranial nerves and artery walls compatible with vasculitis and disturbances in cerebrospinal fluid (CSF) circulation. The patient was treated with ceftriaxone for 2 weeks. Two years later, the patient had an ischemic stroke. Brain magnetic resonance angiography revealed multiple aneurysms, which were not present previously. The largest aneurysm was operated rapidly. The patient was treated with another course of intravenous ceftriaxone for 4 weeks and pulse therapy with corticosteroids. He recovered well. Conclusion. This unique case demonstrates complications of LNB that can result in serious morbidity or even mortality. Lumbar puncture and analysis should be considered for paediatric patients with epileptic seizures or cerebrovascular events living in a Lyme borreliosis endemic area